Revitalisasi Tafsir Balaghi: Telaah al-Shamil fi Balaghat al-Qur’an Karya Muhammad Afifudin Dimyathi - Muh. Yusrol Fahmi; Amru, Khobirul (Bahasa Indonesia, 2022)
This article studies a book al-Sha>mil fi> Bala>ghat al-Qur’a>n and the endeavor of its author, Muhammad Afifudin Dimyathi, in revitalizing the bala>ghi> exegetical studies in Nusantara. Employing a descriptive-analytical method and materials delivered by Afifudin at several occasions, this article attains two main findings. Firstly, the snapshot of al-Sha>mil fi> Bala>ghat al-Qur’a>n at first glance can be understood from three things: the setting of its arrangement, the process of its pre-arrangement, and the process of its arrangement. It is quintessential for whomever to understand those three things in order that the scope, the beginning and the end, and the methodological framework of al-Sha>mil can be comprehended well. Secondly, one of the Afifudin’s endeavors in revitalizing the bala>ghi> exegetical studies in Nusantara is by reasserting and reaffirming the functions of bala>ghah in the context of exegetical Qur’an. In this context, according to him, at least the are five functions of bala>ghah: to reveal the hidden meaning and the implicit meaning from both of the words and the phrases of the Qur’an, to disclose the accuracy of the meaning from the diction of the Qur’an and the secret of its choices, to elucidate the harmony of several words in a verse and of several verses in a surah, to be able to evade misunderstanding or the Qur’an-unwanted understanding, and to help expound mutasha>biha>t verses.